Evaluating AI-powered ChatGPT for intelligent virtual learning environments through conversational intelligence - Isaac Asampana; Henry Akwetey Matey; Ben Ocra; Jones Yeboah Nyame (Institute of Advanced Engineering and Science, 2026)
The rapid advancement of conversational artificial intelligence has transformed virtual learning by enabling intelligent, adaptive, and interactive educational support through natural language communication. Among recent AI technologies, chat generative pre-trained transformer (ChatGPT) has emerged as a powerful conversational intelligence system capable of providing real-time explanations, personalized learning assistance, and contextual academic interactions. This study evaluates the effectiveness of AI-powered ChatGPT in intelligent virtual learning environments through the lens of conversational intelligence. A quantitative survey instrument, developed based on established technology acceptance constructs, was employed to assess users' perceptions of ChatGPT's usefulness, ease of interaction, and educational effectiveness. Using a simple random sampling technique, data were collected from 1,104 participants and analyzed using descriptive statistical methods in SPSS version 25. The results indicate that ChatGPT's conversational capabilities significantly enhance learner engagement, support personalized learning experiences, and improve perceived academic performance through intuitive human-AI interactions. The findings demonstrate that conversational intelligence plays a critical role in improving the effectiveness of intelligent virtual learning environments by facilitating adaptive knowledge delivery and interactive learning support. This study provides valuable insights into the integration of conversational AI technologies for developing next-generation intelligent digital education systems.